2017
DOI: 10.1111/jsr.12635
|View full text |Cite
|
Sign up to set email alerts
|

A review of sleep disturbance in children and adolescents with anxiety

Abstract: The present review examines the relations between sleep disturbance and anxiety in children and adolescents. The review begins with a detailed discussion of normative developmental trends in sleep, and the relation between sleep quality and emotion dysregulation in children. The extant literature on sleep disturbance in clinically anxious children with a focus on subjective versus objective measures of sleep is then summarized in detail. Finally, a review of the reciprocal relationship between sleep and emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 104 publications
(165 reference statements)
10
67
0
4
Order By: Relevance
“…The results indicate that emotional problems and hyperactivity/inattention might be risk factors for sleep problems, though the direction of the relation between sleep problems and emotional problems cannot be confirmed given the cross‐sectional design of the study. This finding is in line with results that have previously been found in healthy children and other populations such as children with ADHD . Similar results were reported by Cohen et al in groups of children with neurological disorders; they concluded that sleep problems are likely more related to behavioral and environmental factors rather than the neurological disorder itself .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results indicate that emotional problems and hyperactivity/inattention might be risk factors for sleep problems, though the direction of the relation between sleep problems and emotional problems cannot be confirmed given the cross‐sectional design of the study. This finding is in line with results that have previously been found in healthy children and other populations such as children with ADHD . Similar results were reported by Cohen et al in groups of children with neurological disorders; they concluded that sleep problems are likely more related to behavioral and environmental factors rather than the neurological disorder itself .…”
Section: Discussionsupporting
confidence: 92%
“…Sleep problems are related to a lower quality of life in children . In longitudinal studies, children with emotional problems such as anxiety and attention problems tend to have more sleep problems . Alternatively, behavioral problems and mood disturbances are negative psychosocial consequences of sleep problems too, as is daytime sleepiness, which can lead to difficulties with focus and attention .…”
Section: Introductionmentioning
confidence: 99%
“…Binary logistic regression analysis identified medical occupation, parental burden, death of a loved one, anxiety and depression as the 5 factors of poor sleep quality. During the SARS outbreak as well, heavy workload, family stress, personal or family lifestyle and negative feelings were significantly correlated with insomnia (23,27,31). Studies have also indicated that high anxiety level correlate with sleep quality (32,33), and a similar association was found in our survey as well.…”
Section: Discussionsupporting
confidence: 86%
“…The first child presented with new-onset anxiety-related sleep disturbance and panic symptoms as his mother, a nurse, worked in a unit dedicated to suspected COVID-19 patients. Reviews of the existing literature show that there is a reciprocal relationship between sleep and emotional regulation in children, and sleep disturbances are highly prevalent in children with anxiety disorders (7). The 10-year-old boy was treated with progressive muscle relaxation training, and there is past evidence that this method is effective in reducing emotional distress in 10-11-year-old children (8).…”
Section: Discussionmentioning
confidence: 99%